Proposed Model of Hybrid-Powered Vehicle: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Traditional bicycles have been recognized as one of the solutions to climate change. It is seenthat the Philippines has challenges with uneven and rough roads to travel on, and cyclists donot want to be exhausted after traveling. The development of hybrid-powered vehicles maybenefit bikers by improving the performance of their bikes on the road.The results of this analysis in terms of motor power, battery, features, efficiency, and batteryare “acceptable.” The acquired overall mean of Electrical Engineers was 3.06, which wasinterpreted as “acceptable,” while the acquired overall mean of Mechanical Engineers was3.07, which was also interpreted as “acceptable.” The t-critical was 3.355, and the t-computedwith a degree of freedom of 8 was 0.068, indicating that there is no significant differencebetween the two groups of respondents. The results of the analysis in terms of cost andmaintenance of e-bike were “least acceptable.” User-friendliness, handling, and performancewere “acceptable.” On the other hand, the results of the analysis in terms of cost,maintenance, user-friendliness, handling, and performance of the proposed model were“acceptable.” The acquired overall mean of the e-bike was 2.71, which was interpreted as“acceptable,” while the acquired overall mean of the proposed model was 2.91, which wasinterpreted as “acceptable.” The t-critical was 3.355, and the t-computed with a degree offreedom of 8 was 1.233, indicating that there is a significant difference between the twogroups of respondents.For further improvement of the study, respondents recommended using a better motor, alarger capacity battery, installing hydraulic brakes to improve handling, faster charging time, aspeed limit of 20kph to minimize serious collisions, and a better tire preference.
Keywords: Engineering